Block cipher based on T-shaped cellular automata - WU Ying-zhi1; HAO Li-bo2; CHEN Ju-hua1 (Tongxin xuebao)
In order to overcome the defect on insecurity of block cipher with few reversible cellular automata, T-shaped cellular automata was proposed, which needed two initial states and applied their characteristics to construct more re-versible cellular automata.A new encryption system based on this class of self-reversible cellular automata was designed.Experiments show that block cipher based on reversible cellular automata not only achieves a better avalanche effect but also improves the security of the applications of cellular automata in cryptography, especially by using pseudo random sequences in the beginning of encryption.